3D printed trabeculae conditionally reproduce the mechanical properties of the actual trabeculae - A preliminary study. Issue 12 (December 2022) - Zheng, Liqin; Huang, Xiuhong; Li, Chihung; Li, Pengfei; Lin, Ziling; Huang, Shaohong
Abstract: Three-dimensional (3D) printing has been used to fabricate synthetic trabeculae models and to test mechanical behavior that cannot be recognized in the actual sample, but the extent to which 3D printed trabeculae replicate the mechanical behavior of the actual trabeculae remains to be quantified. The aim of this study was to evaluate the accuracy of 3D printed trabeculae in reproducing the mechanical properties of the corresponding actual trabeculae. Twelve human trabecular cubes (5 × 5 × 5 mm) were scanned by micro-CT to form the trabecular 3D model. Each trabecular 3D model was scaled ×2-, ×3-, ×4- and ×5-fold and then printed twice at a layer thickness of 60 μm using poly (lactic acid) (PLA). The actual trabecular cubes and the 3D-printed trabecular cubes were first compressed under a loading rate of 1 mm/min; another replicated stack of 3D-printed trabecular cubes was compressed under a strain rate of 0.2/min. The results showed that the stiffness of the printed cubes tended to increase, while the strength tended to converge when the magnification increased under the two loading conditions. The strain rate effect was found in the printed cubes. The correlation coefficient (R 2 ) of the mechanical properties between the printed and actual trabeculae can reach up to 0.94, especially under ×3-, ×4- and ×5-fold magnification. In conclusion, 3D printing could be a potential tool to evaluate the mechanical behavior of actual trabecular tissue in vitro and may help in the future to predict the risk of fracture and even personalize the treatment evaluation for osteoporosis and other trabecular bone pathologies. Abstract : 3D printing; Trabecular bone; Biomechanics; Strain rate; Linear regression.